Andrew Lost in the Ice Age - Greenburg, J. C.; Illustrated by Gerardi, Jan (New York Random House, 2005)
Still trying to stop the evil Dr. Kron-Tox, Andrew, his cousin Judy, Thudd the robot, and Beeper find Uncle Al in the Ice Age, where they encounter prehistoric animals, birds, and people.
Include Illustrations
Keywords: Time travel -- Juvenile fiction